Elucidating the molecular mechanisms underlying the induction of autophagy by antidepressant-like substances in C57BL/6J mouse testis model upon LPS challenge - Przemysław Sołek; Ewelina Czechowska; Magdalena Sowa-Kućma; Katarzyna Stachowicz; Piotr Kaczka; Anna Tabęcka-Łonczyńska (Cell Communication and Signaling, 2023)
Abstract The treatment of depression with pharmaceuticals is associated with many adverse side effects, including male fertility problems. The precise mechanisms by which these agents affect testicular cells remain largely unknown, but they are believed to induce cellular stress, which is sensed by the endoplasmic reticulum (ER) and the Golgi apparatus. These organelles are responsible for maintaining cellular homeostasis and regulating signal pathways that lead to autophagy or apoptosis. Therefore, in this study, we aimed to investigate the autophagy, ER, and Golgi stress-related pathways in mouse testis following treatment with antidepressant-like substances (ALS) and ALS combined with lipopolysaccharide (LPS). We found that most ALS and activated proteins are associated with the induction of apoptosis. However, when imipramine (IMI) was combined with NS-398 (a cyclooxygenase-2 inhibitor) after LPS administration, we observed a marked increase in the BECLIN1, Bcl-2, ATG16L, and LC3 expression, which are marker proteins of autophagosome formation. The expression of the BECN1 and ATG16L genes was also high compared to the control, indicating the induction of autophagy processes that may potentially protect mouse testicular cells from death and regulate metabolism in the testis. Our findings may provide a better understanding of the stress-related effects of specific ALS on the testis. Graphical Abstract Video Abstract